A new GLP-1 analogue with prolonged glucose-lowering activity in vivo via backbone-based modification at the N-terminus. Issue 6 (15th March 2016) - Bai, Xiaohui; Niu, Youhong; Zhu, Jingjing; Yang, An-Qi; Wu, Yan-Fen; Ye, Xin-Shan
Graphical abstract: GLP-1 analogue10 greatly improved the DPP-IV resistance with maintaining good GLP-1R activation in vitro, and showed approximately a 4-fold prolonged blood glucose-lowering activity in vivo in comparison with tGLP-1, which will benefit the development of GLP-1-based anti-diabetic drugs. Abstract: Glucagon-like peptide-1 (GLP-1) is an endogenous insulinotropic hormone with wonderful glucose-lowering activity. However, its clinical use in type II diabetes is limited due to its rapid degradation at the N-terminus by dipeptidyl peptidase IV (DPP-IV). Among the N-terminal modifications of GLP-1, backbone-based modification was rarely reported. Herein, we employed two backbone-based strategies to modify the N-terminus of tGLP-1. Firstly, the amide N -methylated analogues2 –6 were designed and synthesized to make a full screening of the N-terminal amide bonds, and the loss of GLP-1 receptor (GLP-1R) activation indicated the importance of amide H-bonds. Secondly, with retaining the N-terminal amide H-bonds, the β-peptide replacement strategy was used and analogues7 –13 were synthesized. By two rounds of screening, analogue10 was identified. Analogue10 greatly improved the DPP-IV resistance with maintaining good GLP-1R activation in vitro, and showed approximately a 4-fold prolonged blood glucose-lowering activity in vivo in comparison with tGLP-1. This modification strategy will benefit the development of GLP-1-based anti-diabetic drugs.